Molecular Docking study, Synthesis and Preliminary Anti-inflammatory and Antimicrobial of New Conjugate of Quinolone-Phenolic Compounds - Tagreed N-A Omar; Shahad R. Abid-Alkhalik (Iraqi Journal of Pharmaceutical Sciences, 2025)
The carboxylic acid group of quinolones was modified; so, we designed new quinolones derivatives with different antioxidants using Ligand Designer from Glide (Schrodinger LLC). The cap group and the linker were optimized through trying various aliphatic and aromatic residues. A new synthesized derivatives (IIa-Vb) were synthesized by esterification of (ciprofloxacin, gatifloxacin, nalidixic acid and norfloxacin) with antioxidants (a: vanillin, b: sesamol) through a glycol linker. Based on spectral data (NMR, ATR-FTIR) their structure were confirmed. The synthesized compounds were screened for their Pharmacological activities. In vivo, the anti-inflammatory effect of (IIa-Vb) compounds was estimated using a rat paw edema model and showed good activity for the end compounds IIa and IId, and their anti-inflammatory and antimicrobial effects were subsequently evaluated virtually-molecularly analyzed ; all prepared compounds show-interesting activity compared to the DMSO control group (solvent and control).in vitro, their antibacterial and antifungal activities were evaluated at concentrations: (12.5, 25 ,50 &100) mg. using well diffusion method ,for antibacterial activity compared to the reference drug (ciprofloxacin) the results showed significant activity from (IIa, IIb &IIIb) at 12.5 mg, (IIa, IIb ,IIIa ,IIIb,Iva & Vb) at 25 mg , IIIb at 50 mg in case of gram-negative bacteria (Escherichia coli); and (Staphylococcus aureus) (IIa, IIb &IIIb) at 12.5 mg, (IIa, IIb) at 25 mg , IIIb at 50 mg about gram-positive bacteria ,also they shown significant antifungal activity against (Candida albicans) compared with Fluconazole drug:(IIa, IIb and IVb) at (50 and 100) mg, (IIb) at 25 mg. ADMET analysis of quasi-active molecules was performed and demonstrated an acceptable drug-like profile and desirable pharmacokinetic properties.